Status of integrated pest management (IPM) in SAARC countries - Ahmed, Awwal; SAARC Agricultural Information Centre (Dhaka : SAARC Agriculture Centre, 2009)
Contributed articles.
Includes bibliographical references and index.
Keywords: Pests -- Integrated control -- South Asia